Oat, wheat and sorghum cultivars for the management of Meloidogyne enterolobii - De Brida, Andressa Lima [UNESP]; Castro, Bárbara Monteiro De Castro E; Zanuncio, José Cola; Serrão, José Eduardo; Wilcken, Silvia Renata Siciliano [UNESP] (Brill Academic Publishers, 2018)
Meloidogyne enterolobii, reported in different regions of Brazil, is a polyphagous nematode parasitising plants resistant to other root-knot nematode species. This study evaluated the resistance of six cultivars of Avena sativa, seven cultivars of Triticum aestivum and 13 hybrids of Sorghum bicolor to M. enterolobii. The experiment was conducted in a glasshouse. The soil was autoclaved and infested with 5000 eggs of M. enterolobii. The tomato 'Rutgers' was used as the susceptible standard to this nematode. The indices of galls, egg masses, and reproduction factor of M. enterolobii were evaluated 60 days after inoculation. This nematode did not reproduce in any of the genotypes considered resistant. The oat, wheat and sorghum cultivars studied may be recommended for crop rotation in areas infested with M. enterolobii.
Keywords: Avena sativa; control; crop rotation; nematode; resistance; root-knot nematode; Sorghum bicolor; Triticum aestivum